Design and integration of a drone based passive manipulator for capturing flying targets. Issue 7 (6th July 2022) - Vidyadhara, B. V.; Tony, Lima Agnel; Gadde, Mohitvishnu S.; Jana, Shuvrangshu; Varun, V. P.; Bhise, Aashay Anil; Sundaram, Suresh; Ghose, Debasish
SUMMARY: In this paper, we present a novel passive single degree-of-freedom (DoF) manipulator design and its integration on an autonomous drone to capture a moving target. The end-effector is designed to be passive, to disengage the moving target from a flying UAV and capture it efficiently in the presence of disturbances, with minimal energy usage. It is also designed to handle target sway and the effect of downwash. The passive manipulator is integrated with the drone through a single DoF arm, and experiments are carried out in an outdoor environment. The rack-and-pinion mechanism incorporated for this manipulator ensures safety by extending the manipulator beyond the body of the drone to capture the target. The autonomous capturing experiments are conducted using a red ball hanging from a stationary drone and subsequently from a moving drone. The experiments show that the manipulator captures the target with a success rate of 70% even under environmental/measurement uncertainties and errors.